Agroecological efficiency of periodic use of neutralized phosphogypsum in rice crops - Vizirskaya Maria; Sheydgen Ashad; Akanova Natalia; Zhdanov Vasilii; Tihonova Maria; Buzylev Alexey (E3S Web of Conferences, 2020)
The purpose of the experiment was to study the influence of periodic using of neutralized phosphogypsum on the fertility of meadow chernozem soils of Krasnodar Territory, achieving of the appropriate level of rice agrocenosis productivity, and the quality of rice grain. The timing of the effective use of phosphogypsum as a phosphorus fertilizer was revealed during the experiment. It was proved that the same level of mobile phosphorus content in rice soils can be achieved by using either phosphogypsum or standard phosphorus-containing fertilizers. Given the fact that nitrogen and potassium fertilizers are already used, using of phosphogypsum provides an opportunity of getting a 6,34 tons/hectare yield of rice (the same result was achieved using N120P80K60 fertilizer). 3 years after re-fertilizing the soil with phosphogypsum we can notice that effectiveness of phosphogypsum in optimization of rice mineral nutrition program contributes to cost savings of 4155 RUB/hectare in comparison with traditional fertilizing system.